2010
DOI: 10.1371/journal.pone.0014427
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analysis of the Arlequin Mutant Corroborates the Essential Role of the ARLEQUIN/TAGL1 Gene during Reproductive Development of Tomato

Abstract: Reproductive development of higher plants comprises successive events of organ differentiation and growth which finally lead to the formation of a mature fruit. However, most of the genetic and molecular mechanisms which coordinate such developmental events are yet to be identified and characterized. Arlequin (Alq), a semi-dominant T-DNA tomato mutant showed developmental changes affecting flower and fruit ripening. Sepals were converted into fleshy organs which ripened as normal fruit organs and fruits displa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
119
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 106 publications
(125 citation statements)
references
References 84 publications
4
119
0
2
Order By: Relevance
“…A similar phenotype was found in TAGL1 silenced tomatoes, which also showed reduced firmness although ethylene production and lycopene accumulation were defective, and reduced pericarp thickness and the thinner cuticle layer were postulated as a possible explanation of the softening. 16,18) We observed lower expression of the genes involved in cuticle biosynthesis in the pre-ripening stage fruit of the suppressed line. FUL2 is expressed strongly at the pre-ripening stage, but FUL1 is not, 20) suggesting that FUL2 is responsible for cuticle biosynthesis before ripening.…”
Section: Ful1 and Ful2 Regulate Tomato Fruit Ripening Via Upregulatiomentioning
confidence: 71%
See 2 more Smart Citations
“…A similar phenotype was found in TAGL1 silenced tomatoes, which also showed reduced firmness although ethylene production and lycopene accumulation were defective, and reduced pericarp thickness and the thinner cuticle layer were postulated as a possible explanation of the softening. 16,18) We observed lower expression of the genes involved in cuticle biosynthesis in the pre-ripening stage fruit of the suppressed line. FUL2 is expressed strongly at the pre-ripening stage, but FUL1 is not, 20) suggesting that FUL2 is responsible for cuticle biosynthesis before ripening.…”
Section: Ful1 and Ful2 Regulate Tomato Fruit Ripening Via Upregulatiomentioning
confidence: 71%
“…These phenotypes in the FUL1/FUL2 suppressed fruits, a failure of ripening but reduced firmness, were similar to TAGL1 suppressed lines. [16][17][18] Because TAGL1 suppression reduced the accumulation of cuticle on the peel, 16,18) we analyzed cuticle accumulation in the FUL1/FUL2 suppressed fruits. We found that the FUL1/FUL2 suppressed fruits had a thinner layer of cuticle than the rin mutant fruits (Fig.…”
Section: Suppression Of Ful1 and Ful2 Inhibited Tomato Fruit Ripeningmentioning
confidence: 99%
See 1 more Smart Citation
“…Using RNA interference (RNAi), transgenic plants with reduced TAGL1 expression produced fruit that showed varying degrees of defects in ripening (Vrebalov et al 2009;Pan et al 2010;Gimenez et al 2010). Similar ripening phenotypes were observed in a study utilizing virus-induced gene silencing and an ERF-associated amphiphilic repression motif to overexpress TAGL1 as a dominant repressor (Itkin et al 2009).…”
Section: Phenotypic Analyses Reveal Canonical and Novel Tagl1 Functionsmentioning
confidence: 67%
“…Several studies over the past few years have examined the role of the TAGL1 gene in controlling many aspects of tomato fruit ripening (Itkin et al 2009;Vrebalov et al 2009;Pan et al 2010;Pineda et al 2010;Gimenez et al 2010Gimenez et al , 2015Gimenez et al , 2016. Using RNA interference (RNAi), transgenic plants with reduced TAGL1 expression produced fruit that showed varying degrees of defects in ripening (Vrebalov et al 2009;Pan et al 2010;Gimenez et al 2010).…”
Section: Phenotypic Analyses Reveal Canonical and Novel Tagl1 Functionsmentioning
confidence: 99%